2017
DOI: 10.1063/1.4994997
|View full text |Cite
|
Sign up to set email alerts
|

Novel doping alternatives for single-layer transition metal dichalcogenides

Abstract: Successful doping of single-layer transition metal dichalcogenides (TMDs) remains a formidable barrier to their incorporation into a range of technologies. We use density functional theory to study doping of molybdenum and tungsten dichalcogenides with a large fraction of the periodic table. An automated analysis of the energetics, atomic and electronic structure of thousands of calculations results in insightful trends across the periodic table and points out promising dopants to be pursued experimentally. Be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…For the 3 × 3 supercell MoS 2 ML with one Mo substituted by Nb atom (Nb 1 ), the Nb tends to substitute the Mo atom instead of the S atom for both rich Mo and S cases, consistent with the tendency reported in previous researches [16][17][18][19][20] . The Nb 1 substituted MoS 2 ML is also proved to be dynamically stable (without imaginary frequency) through the density functional perturbation theory (DFPT) 21 .…”
Section: Resultssupporting
confidence: 89%
“…For the 3 × 3 supercell MoS 2 ML with one Mo substituted by Nb atom (Nb 1 ), the Nb tends to substitute the Mo atom instead of the S atom for both rich Mo and S cases, consistent with the tendency reported in previous researches [16][17][18][19][20] . The Nb 1 substituted MoS 2 ML is also proved to be dynamically stable (without imaginary frequency) through the density functional perturbation theory (DFPT) 21 .…”
Section: Resultssupporting
confidence: 89%
“…1,[51][52][53] Whereas a lot of progress has been reported and reviewed on the synthesis of 2D-TMD sheets, 16,50,[54][55][56] seemingly, relatively less work has been focused on the second critical aspect, which is nevertheless a veritable bottleneck to the incorporation of 2D TMDs in (opto)electronic technologies. 1,[51][52][53] Achieving a systematic control over charge-carrier doping is essential for minimizing detrimental Schottky barriers at metalsemiconductor interfaces, 57 as well as for manufacturing p-n junctions and transistors with reproducible electrical characteristics, which are crucial requirements for the production of complementary-logic devices and circuits. 58 Conventional doping techniques, such as ion implantation and dopant diffusion, are extremely challenging to be implemented in combination with 2D TMDs, since damages/defects induced by such processes in ultrathin crystals can have drastic effects on their structural and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Singh et al [78] revealed that substitutional doping of 3d transition-metal atoms (Ti, V, Cr, Mn, Fe, Co, and Ni) at the W site is feasible by calculating the binding energy based on the density functional theory. Furthermore, Onofrio et al [79] used DFT to investigate WS 2 with a large section of the periodic table. The calculation results proved that doping with early transition metals (TMs) results in the tensile strain of WS 2 and a significant reduction of the band gap.…”
Section: Dopingmentioning
confidence: 99%